Recommandations - Rudesse (Facebook, 2020)
Keywords: Bibliographie; Dans le rapport; Sophie-Anne

Comedy in the Era of #MeToo: Masking and Unmasking Sexual Misconduct in Stand-Up Comedy - Oppliger, Patrice; Mears, Kathryn (The Dark Side of Stand-Up Comedy, 2020)
With the announcement of allegations of sexual harassment and sexual assault against beloved comedians, we ask, “Can one separate the art from the artist?” Comedians are supposed to bring audiences joy and laughter; however, this role is challenged when there is incongruity between the comic persona and the real-life misdeeds of comedians. We explore the rise of the #MeToo movement and the role of comedy in exposing as well as masking allegations against Bill Cosby, Louis C.K., Al Franken, and Aziz Ansari. Guided by disposition theory and disengagement models, findings reveal factors of race, gender, and personal relationships appear to influence comedians’ assessment of fellow comedians accused of sexual misconduct. Audience members also appear to experience moral disengagement.
Keywords: Bibliographie; Nettoyer; Sophie-Anne

Louis C.K.’s time’s up time out: rereading persona post-scandal - Piper, Melanie (Celebrity Studies, 2020)
Keywords: Bibliographie; Nettoyer; Sophie-Anne

Rapport de recherche sur l'état du milieu du spectacle d'improvisaiton théâtrale au Québec - Garneau, Jocelyn (Le théâtre de la Ligue Nationale d'Improvisation et la Rencontre Théâtre-Ados de Lavac avec l'appui financier du Ministère de la Culture et des Communications du Québec, 2020)
Keywords: Bibliographie; Nettoyer; Sophie-Anne

Can You Come Back from Being Cancelled? A Case Study of Podcasting, Cancel Culture, and Comedians during #MeToo - Holman, Kylie J. (University of Nebraska, 2020)
Cancel culture is a new phenomenon of public shaming, facilitated by social media. This type of public shaming is accepted due to the alleged transgression of those who are cancelled. Social understanding of cancel culture does not generally allow for redemption. Using the theoretical framework of Feminist Media Studies (Van Zoonen, 1994) and Media Framing Theory (Gitlin, 1980), this study reveals the media’s role and power in the cancelling process. This study utilized a mixed-methods approach of case study and text analysis of episodes from the pop culture and politics podcast, Keep It. The case study focused on podcast episodes pertaining to two comedians cancelled for allegations of sexual misconduct in the #MeToo era [Oct. 2017 – Present]: Aziz Ansari and Louis C.K. The study also provided comparative cases of other comedians and comedic actors who were cancelled. Findings add to our understanding of cancel culture and appropriate methods of redemption for those who are cancelled.
Keywords: #MeToo; Bibliographie; Cancel culture; Comedians; Nettoyer; Podcasting; Redemption; Sophie-Anne

Le point de vue des improvisatrices au sujet des inégalités et des stéréotypes de genre véhiculés en improvisation théâtrale et ce que ceux-ci révèlent sur la société : Une recherche en travail social féministe - Robert Durant, Catherine (Université du Québec à Montréal, 2020)
Keywords: Bibliographie; Coffre à outils; Nettoyer; Sophie-Anne